High-k Structures in 124Cs - 杨东 陆景彬 刘运祚 马克岩 王辉东 王烈林 刘弓冶 李黎 马英君 竺礼华 吴晓光 李广生 贺创业 (等离子体科学和技术：英文版, 2012)
High spin states in the odd-odd nucleus 124Cs have been investigated through the fusion-evaporation reaction 116Sn（11B, 3n）l24 Cs with a beam energy of 45 MeV. A new rotational band is established and assigned as the high-k configuration of πg9/2140419/2＋ ⊙vh 11/2[523]7/2-. Some structures linking to this band have also been observed. According to the results of the excitation energy systematics, the lowest level of this band is assigned as 9-, and the 8- isomer bandhead has not been observed. Another isomer with a half life of 6.3 s has also been observed with its new decay paths established, Its excitation energy is raised by 79 keV, but its Iπ is not changed.